(untitled) - Đỗ, Tuấn Minh (Hà Nội, 2012)
This book talking about greeting and introduction, asking about personal information, things around us, a nice flat, likes and dislikes...
Keywords: English language,Tiếng Anh,Tiếng Anh,English language; Study and teaching,Foreign speakers,Câu hỏi và bài tập,Giảng dạy và học tập,Người nước ngoài,Problems, exercises, etc